2005
DOI: 10.1167/iovs.03-1213
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Visual Involvement in Multiple Sclerosis: A Study by MRI, VEPs, Frequency-Doubling Perimetry, Standard Perimetry, and Contrast Sensitivity

Abstract: In patients affected by clinically definite MS without history of optic neuritis and no visual symptoms, there is a large prevalence of visual pathway involvement that can be diagnosed only by performing multiple tests. The comparison of the tests is also useful to detect the presence of multiple lesions in the same patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 18 publications
5
84
0
3
Order By: Relevance
“…Some studies have shown the presence of subclinical optic neuropathy in MS patients, which can be diagnosed by performing not only OCT, but such multiple tests as visual evoked potentials, visual field examination, visual acuity, and colour vision. [25][26][27] According to the literature, in the early stages of ON in MS patients, RNFL and macular thinning or thickening (swelling) can occur, along with different structural changes in optic disc morphology. 27,28 The retina in MS patients passes through stages of minimal demyelination, remyelination, and gliosis, which can be verified only by biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the presence of subclinical optic neuropathy in MS patients, which can be diagnosed by performing not only OCT, but such multiple tests as visual evoked potentials, visual field examination, visual acuity, and colour vision. [25][26][27] According to the literature, in the early stages of ON in MS patients, RNFL and macular thinning or thickening (swelling) can occur, along with different structural changes in optic disc morphology. 27,28 The retina in MS patients passes through stages of minimal demyelination, remyelination, and gliosis, which can be verified only by biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the common conclusion is that MS patients have more visual complaints and a variety of ophthalmological abnormalities that warrant comprehensive examination. As reported by Sisto et al 24 , no single ophthalmic test would be able to detect all the subclinical abnormalities present in MS eyes. The recent work of Mowry et al 25 also points towards the use of different and meaningful ophthalmological measures in order to better interpret the visual impairment and visual-related quality of life in MS.…”
Section: Resultsmentioning
confidence: 88%
“…Hastalarda genelikle MD değişikliklerinde geniş prevelansın eşlik ettiği diffüz tip kayıpla birlikte daha az oranda santral 10° ve 20°'ye uzanan merkezi depresyon, derin santral skotom, parsiyel sağ homonim hemianopsi, parsiyel sol homonim hemianopsi tarzında görme alanı defektleri bildirmişlerdir. 19 Çalışmamızda MD ve PSD değerlerinde kontrol grubu ile diğer gruplar arasında istatistiksel olarak anlamlı bir fark mevcuttu. MD ve PSD düzeyindeki değişikliklere %80 oranında diffüz tip GA kaybı eşlik etmekteydi.…”
Section: Discussionunclassified